Recent progress in biomaterials for heart valve replacement: Structure, function, and biomimetic design. Issue 6 (17th June 2021) - Shao, Ziyu; Tao, Tingting; Xu, Hongfei; Chen, Cen; Lee, In‐Seop; Chung, Sungmin; Dong, Zhihui; Li, Weidong; Ma, Liang; Bai, Hao; Chen, Qianming
Abstract: Heart diseases caused by structure and function degradation is troubling millions of people all over the world. With the extension of human lifespan, the demand for heart valve replacement is rapidly increasing. However, the currently used prostheses of heart valve in clinic such as mechanical and tissue valves all have serious limitations over long‐term stability after implanting. Therefore, novel artificial heart valves with outstanding durability and low degradation risk are still in great demands, despite of numerous studies in the literature. The sophisticated, multiscale structure of native heart valve is believed to be the key to its mechanical and biological durability during long‐term cyclic motion. In this review, we discussed the complex structure of the native heart valve as well as their contributions to the valve's cyclic work. In addition, representative and state of the art studies of biomimetic heart valves inspired by the natural valve are also introduced. Based on these, the structural and functional design of future novel biomimetic heart valves are proposed. Abstract : Summary of the review : A brief introduction of the complex structure of the native heart valve as well as their contributions to the valve's cyclic work. Summary of state of the art studies of biomimetic heart valves inspired by native heart valve.